Determination of Vitamin E in Canola Seeds by High Performance Liquid Chromatography - Karasakal, Ayca; Yalcin Gurkan, Yelda (Asian Journal of Chemistry, 2012)
Tocopherols (vitamin E) are natural phenolic antioxidants present in vegetable oils and are responsible for many healthful properties of these foods. They are effective radical scavengers and defend the body against free radical attack by protecting polyunsaturated fatty acids. Vitamin E plays an important role at the intracellular level since its deficiency increases membrane fragility and promotes the damage of membranes by oxygen-reactive species, ozone or other free radicals. The tocopherols belong to a group of structurally related compounds called tocols. Foods such as nuts, seeds, some grains and vegetable oils are good sources of natural tocopherol antioxidants. The various tocopherols may exist in a free or a esterified form. In seed oils, they are mainly present in the free state and the level of antioxidant materials is of great importance in the stability of vegetable oil products. It is known that vitamin E activity decreases while the antioxidant activity increases in the order a-, b-, g- and d-tocopherols. Canola is one of the most important oil seeds growing in many parts of the world. It is very important to grow canola with high oil levels for agronomical benefits. There is a growing interest for the use of oil seeds for nutritional, industrial and pharmaceutical usages. The world production of canola oil is higher than soybean and sunflower. In this study an effective high performance liquid chromatography method for measuring a-tocopherol in canola gathered from different regions.